Characterization of the novel HLA‐A*03:315 allele by sequencing‐based typing. (3rd December 2018) - Cargou, Marine; Elsermans, Vincent; Top, Isabelle; Guidicelli, Gwendaline; Visentin, Jonathan
Abstract : HLA‐A*03:315 differs from HLA‐A*03:01:01:01 by one nucleotide substitution at codon 285 in exon 5.